Evaluating the Problems of Population Resettlement from the Construction of Shiroro Hydropower Project, Nigeria - H.M, Liman; D.D, Abraham; Y.M, Suleiman (Journal of Environments, 2015)
This study focused on the evaluation on the problems of population Resettlement from the construction of Shiroro Hydropower Project, Nigeria. Two villages (Zumba and GaladimaKogo) directly affected, were selected for the household questionnaire survey and interview schedule. The results indicates that environmental problems such as deforestation, erosion, land degradation and flooding as major problems affecting the livelihood of the communities in the study area were identified. The presence of the lake increased the rate and incidence of water-related diseases such as malaria, Cholera, river blindness and bilharzias. With respect to resettlement only 46% of the populations were compensated, the remaining 54% are yet to be compensated 24 years after the dam commenced operation. Conclusively, the people were only evacuated and displaced from their ancestral homes without been properly resettled and compensated for their social, economic and material loses. It is recommended that dam operators and regulatory authorities meet up their commitments to properly resettle and compensate the affected communities.